Tradition and Modernity — Experiences of Rural Sikh Girls in Ferozepur, Punjab - Bassi, Tripti (THE PRIMARY TEACHER, 2017)
This paper presents a linkage between tradition and modernity with reference to the Sikh Kanya Mahavidyalaya at Ferozepur, Punjab. The school was established in 1892 in old Ferozepur city as an all-girls’ school. It is now a co-ed school till Class VIII and an all-girls’ school till the senior secondary stage. Based on ethnographic research, the paper brings together experiences and reflections of girls in this border region of India. It discusses aspects related to gurmat education and the way it propagates religious identities. Education that is transacted inculcates both traditional, as well as, modern values among girls. They either learn to play their traditional roles better or develop skills required for modern professions. Often, tradition and modernity coexist shaping up the identity of girls in varied ways, thereby, enabling them to often resolve inner and outer conflicts with strength and fortitude. The paper aims to highlight the complex interface among the forces of education, religion and gender.